Immunogenicity of the biosimilar CT-P13 infliximab or the original infliximab in Iraqi patients with Ankylosing spondylitis does not correlate with their demographic characteristics - M. Kamil, Mohammed; Jabarah, Mohammed Abdul- Hassan; A.l. Jasim, Nizar (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Ankylosing spondylitis is a rare disease affecting people with hereditary factors. Its treatment includes life style modification and use of drugs such as the biologic agent infliximab or its biosimilar, CT-P13 infliximab. Despite their therapeutic usefulness, these agents are associated with a number of serious adverse effects such as immunogenicity. Objectives: The aim of current study was to investigate if immunogenicity of the biosimilar CT-P13 infliximab or the original infliximab, in Iraqi patients with Ankylosing spondylitis, is affected by any of the patients’ demographic characteristics. Methods: A retrospective open-label study was conducted from December 2021 to March 2022 at the Rheumatology Unit, Baghdad Teaching Hospital/Medical City, Baghdad. Forty-four patients were taking Infliximab, and another 50 patients were taking CT-P13, both at a dose of 5mg/kg for 3 months prior to recruitment in current study. Disease activity was assessed by ASDAS-CRP score while antibodies and C-reactive protein were tested by Enzyme-Linked Immunosorbent Assay technique. Statistical analyses were performed using SPSS statistical package for Social Sciences version 20.0. The level of significance was considered at P<0.05. Results: There was non-significant correlation between anti-infliximab antibodies and demographic data of patients (P>0.05). Similar data were reported regarding the biosimilar CT-P13 infliximab except for smoking and disease activity which exhibited significant correlation with development of anti-CT-P13 antibodies (P<0.05). Conclusion: Immunogenicity of the biosimilar CT-P13 infliximab, but not that of the original Infliximab, may be influenced by demographic characteristics or disease activity in patients with ankylosing spondylitis.